Identifikasi Timbulan, Komposisi, Karakteristik, dan Potensi Daur Ulang Sampah Pertanian Tanaman Pangan di Kabupaten Lima Puluh Kota - Nada Zhafirah Hendria; Yommi Dewilda; Rizki Aziz (Fakultas Teknik, 2023)
Abstract Lima Puluh Kota District is one of the dominant food crop-producing provinces in West Sumatera. This activity produces an amount of waste. The research was conducted at 15 points in the sub-district Lareh Sago Halaban with a purposive sampling method and based on SNI 19-3964-1994. The results showed the pre-harvest waste generation was 12,024,480 tons/year or 168,255,706 m3/year, whereas the post-harvest waste generation was 1,283,828,005 tons/year or 17,664,025,689 m3/year. The pre-harvest waste compositions 46.835% agricultural waste, 25.194% rubbish, and 28.020% agricultural hazardous waste, though the post-harvest waste was 100% agricultural waste. Physical characteristics obtained 0.232 kg/L of pre-harvest waste and 0.052 kg/L of post-harvest waste. Chemical characteristics equally proximate analysis with water content 36.9538%, volatile content 61.0327%, ash content 1.4870%, fixed carbon 0.5265%, and the C/N ratio obtained 18.0797. The biodegradability fraction was 65,7044%. The potential for recycling the pre-harvest waste was 52.413%, while the post-harvest waste was 100%. The recommendations will probably give, like reducing waste from chemical fertilizer packaging with organic fertilizer, utilizing packaging waste as a substitute for polybags, processing plant waste into compost, and processing agricultural hazardous waste to third parties.Keywords: characteristic, composition, food crop waste, recycling potentials, waste generation